A novel single-phase ZCS-PWM high-power-factor boost rectifier - Canesin, C. A.; Barbi, I (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This paper presents a novel single-phase high-power-factor (HPF) pulsewidth-modulated (PWM) boost rectifier featuring soft commutation of the active switches at zero current (ZC), It incorporates the most desirable properties of conventional PWM and soft-switching resonant techniques.The input current shaping is achieved with average current mode control and continuous inductor current mode.This new PWM converter provides ZC turn on and turn off of the active switches, and it is suitable for high-power applications employing insulated gate bipolar transistors (IGBT's),The principle of operation, the theoretical analysis, a design example, and experimental results from a laboratory prototype rated at 1600 W with 400-Vdc output voltage are presented. The measured efficiency and the power factor were 96.2% and 0.99%, respectively, with an input current total harmonic distortion (THD) equal to 3.94%, for an input voltage with THD equal to 3.8%, at rated load.
Keywords: AC DC converter; active power-factor correction; soft-commutation technique